DEVELOPMENT AND EFFECTIVENESS OF DIGITAL APPLICATION AS THE NEW SYSTEM TO ORGANIZE PRACTICUM MATERIALS AT SCHOOL OF PROSTHETICS ORTHOTICS IN POLYTECHNIC HEALTH SCIENCES JAKARTA I - Nazier, Suci Anatasia; Triyani, Triyani; Annisa, Rizki; Gayatri, Padma Vidya; Putra, Raden Achmad Candra (Quality : Jurnal Kesehatan, 2023)
Introduction: The Prosthetic Orthotics (PO) School at Health Polytechnic Jakarta I relies on practical skills and various materials in its labs/workshops for device fabrication. To enhance logistics management, this study proposes a new digital application leveraging digital technology's efficiency. The aim is to improve the organization of logistics at the PO school, given the diversity and volume of practicum materials. The study involves developing and evaluating the effectiveness of the new digital application. Method: Using a mixed methods approach, the study employed a focus group discussion (FGD) to gather insights from managerial-level participants and student users. FGD participants discussed the expected design, features, and functions of the new digital management system, as they are actively involved in logistic management. The study also evaluated the new system by comparing it with the old manual system. Results and Conclusion: Participants expressed expectations for a digital application with user-friendly features, easy gadget access, access authorization, automation of stock tracking, and a warning system for stock shortages. The developed digital management system aligned with these expectations and demonstrated superior effectiveness when compared to the manual system in managing a diverse range of practicum materials at the PO School of Health Polytechnic Jakarta I. Time constraints during the COVID-19 lockdown limited the elaboration of additional key features, suggesting a need for future studies to explore other aspects based on the school's evolving needs.